2012
DOI: 10.1097/jsm.0b013e31823403d2
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Age Differences in Depression and Baseline Sport-Related Concussion Neurocognitive Performance and Symptoms

Abstract: Athletes with severe depression scored lower on visual memory than those with minimal depression. Athletes with severe depression report more concussion symptoms than athletes with minimal and moderate depression scores. Symptoms of depression should be included in baseline assessments to help disentangle depression from concussion symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
131
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(148 citation statements)
references
References 22 publications
12
131
5
Order By: Relevance
“…Despite the fact that Covassin et al 13 found no differences between age groups and a number of conflicting results, we based our hypothesis on the most recent CIS consensus statement that regarded age as a predictor of a protracted recovery. We hypothesized that younger athletes, compared with older athletes, would: 1) endorse more symptoms postconcussion, 2) endorse increased symptom severity postconcussion, and 3) experience increased average time to return to symptom baseline as measured by the Total Symptom Scale (TSS).…”
Section: ©Aans 2013mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that Covassin et al 13 found no differences between age groups and a number of conflicting results, we based our hypothesis on the most recent CIS consensus statement that regarded age as a predictor of a protracted recovery. We hypothesized that younger athletes, compared with older athletes, would: 1) endorse more symptoms postconcussion, 2) endorse increased symptom severity postconcussion, and 3) experience increased average time to return to symptom baseline as measured by the Total Symptom Scale (TSS).…”
Section: ©Aans 2013mentioning
confidence: 99%
“…23 Controversy exists regarding the relationship between age and symptoms of concussion. Covassin et al 13 tested 837 college and 779 high school athletes and found that high school athletes reported more baseline somatic/migraine symptoms than college athletes, whereas college athletes reported more emotional and sleep symptoms than high school athletes. 13 All participants with a history of TBI were excluded, and return to baseline symptoms after SRC was not investigated.…”
Section: ©Aans 2013mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, when investigating actual reporting behavior, found gender differences in the reporting of actual symptoms in a mixed high-school (n=150)/college athlete (n=72) cohort, with female athletes reporting more symptoms than male athletes at baseline and up to 14 days post concussion. A larger study by Covassin, Elbin III, et al (2012) involving athletes in high school (n=779) and college (n=837) observed no differences in concussion symptom reporting between genders. Similarly, Llewellyn, Burdette, Joyner, and Buckley (2014) reported no differences between gender in reporting of concussion symptoms.…”
Section: Influence Of Gender On Continuing To Play And/or Not Reportmentioning
confidence: 99%
“…A growing body of research has investigated differences in concussion and related outcomes between males and females (Colvin et al, 2009;Covassin, Elbin III, Larson, & Kontos, 2012;Covassin, Elbin, Harris, Parker, & Kontos, 2012;Covassin, Swanik, & Sachs, 2003). As a result Corvassin and colleagues Covassin et al, 2003) have proposed that women are at higher risk for concussion than men.…”
Section: Influence Of Gender On Continuing To Play And/or Not Reportmentioning
confidence: 99%